2001
DOI: 10.1074/jbc.m106127200
|View full text |Cite
|
Sign up to set email alerts
|

MM-1, a c-Myc-binding Protein, Is a Candidate for a Tumor Suppressor in Leukemia/Lymphoma and Tongue Cancer

Abstract: The c-myc oncogene product (c-Myc) is a transcription factor that dimerizes with Max and recognizes the E-box sequence, and it plays key functions in cell proliferation, differentiation, and apoptosis. We previously showed that MM-1 bound to myc box II within the transactivation domain of c-Myc and repressed the E-box-dependent transcriptional activity of c-Myc. Here we report that MM-1 showed features of a tumor suppressor. In an EST data base search for cDNAs homologous to MM-1, we found a frequent substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 41 publications
4
56
0
1
Order By: Relevance
“…MM-1␣ is a novel tumor suppressor that inhibits transcriptional and transforming activities of c-Myc by recruiting the HDAC1 complex via TIF1␤/KAP1, a transcriptional corepressor (12)(13)(14)(15). MM-1␣ is also a subunit of the molecular chaper-FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MM-1␣ is a novel tumor suppressor that inhibits transcriptional and transforming activities of c-Myc by recruiting the HDAC1 complex via TIF1␤/KAP1, a transcriptional corepressor (12)(13)(14)(15). MM-1␣ is also a subunit of the molecular chaper-FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
“…Other PFD Subunits-MM-1␣ has dual functions as a transcriptional modulator through the c-Myc-TIF1␤ pathway (12)(13)(14)(15) and as a subunit, PFD5, of the chaperone prefoldin (2). To examine the behavior of MM-1␣ when PFD complex formation is inhibited, siRNAs targeting PFD2 (siPFD2), MM-1a/PFD5 (siMM-1␣) as a positive control or luciferase (siLuc) as a negative control were transfected into human HeLa, H1299 and HepG2 cells and into mouse embryonic fibroblasts (MEF), Neuro-2a and NIH3T3 cells, and the protein levels of MM-1␣ and PFD2 were examined by Western blotting with respective antibodies.…”
Section: Knockdown Of Pfd Subunit Expression Decreases the Levels Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, ectopic expression of RPC32α in the partially transformed IMR90 cell lines increased the expression of genes, including S100A4 (23), replication factor C subunit RFC40 (24), EZRIN (25) and RAC1 (26), that previously have been associated with cell survival, tumor growth and metastasis. Furthermore, ectopic expression of RPC32α reduced expression of genes with reported tumor suppressor activity, such as PREFOLDIN 5 (MM-1) (27) or KLF6 (28), when compared either with partially transformed IMR90 cells or with partially transformed IMR90 cells with ectopically expressed RPC32β ( Fig. 4B and Table S2).…”
Section: Ectopic Expression Of Rpc32α Strongly Influences the Expressmentioning
confidence: 99%
“…tion, including transcriptional regulation for PFD5 (49,50) and PFD4 (51) and DNA binding activity for PFD1 and PFD2 (52), and that there are some distinctive phenotypes between PFD1-null and PFD5-L110R mice (47,48). PFD5/MM-1 is known to act as a c-MYC-binding protein that suppresses cell growth and transformation independently of the prefoldin complex (49,53). Furthermore, Tang et al (54) have reported that the expression level of PFD5 mRNA was up-regulated in HTTQ300-expressing mice (R6/2) despite the fact that mRNA levels of other subunits were unaffected.…”
Section: ϫ5mentioning
confidence: 99%